A new marine tardigrade species (Heterotardigrada: Batillipedidae) from the southeast coast of India - Vishnudattan, N. K.; Rubal, Marcos; Nandan, S. Bijoy (Zootaxa, 2024)
A new marine tardigrade species, Batillipes chandrayaani sp. nov. is described from the sandy mid littoral region of the southeast coast of India. This novel species can be distinguished from all its congeners by the presence of a dorsal indentation in the anterior cephalic region, shape of primary clavae, presence of secondary clavae, segmented dorsal body due to the presence of transverse cuticle folds, shape of leg IV sensory organ with the presence of two van der Land’s organs, long hook shaped lateral body projections on the caudal segment and the presence of a semi-circular cuticular projection on the coxal region of leg II and leg III.